Synthesis and anticancer activities of novel 8-azapurine carbocyclic nucleoside hydrazones. Issue 20 (15th October 2015) - Wang, Yeming; Yan, Hong; Ma, Chao; Lu, Dan
Graphical abstract IC50 = 11.69 μM (human liver cancer Huh-7 cell line).